Lost at high latitudes: Arctic and endemic plants under threat as climate warms. Issue 5 (27th January 2019) - Niskanen, Annina Kaisa Johanna; Niittynen, Pekka; Aalto, Juha; Väre, Henry; Luoto, Miska
Abstract: Aim: Species' biogeographical patterns are already being altered by climate change. Here, we provide predictions of the impacts of a changing climate on species' geographical ranges within high‐latitude mountain flora on a sub‐continental scale. We then examined the forecasted changes in relation to species' biogeographic histories. Location: Fennoscandia, Northern Europe (55–72°N). Methods: We examined the sensitivity of 164 high‐latitude mountain species to changing climate by modelling their distributions in regard to climate, local topography and geology at a 1 km 2 resolution. Using an ensemble of six statistical modelling techniques and data on current (1981–2010) and future (2070–2099) climate based on three Representative Concentration Pathways (RCPs 2.6, 4.5, 8.5), we developed projections of current and future ranges. Results: The average species richness of the mountain flora is predicted to decrease by 15%–47% per 1 km 2 cell, depending on the climate scenario considered. Arctic flora is projected to undergo severe range loss along with non‐poleward range contractions, while alpine flora is forecasted to find suitable habitat in a warmer North. A substantial majority (71%–92%) of the studied species are projected to lose more than half of their present range by the year 2100. Species predicted to lose all suitable habitat had ranges centred in the northernmost (>68°N) part of continental Europe. Main conclusions: Climate change is predicted to substantially diminish the extent and richness of Europe's high‐latitude mountain flora. Interestingly, species' biogeographic histories affect their vulnerability to climate change. The vulnerability of true Arctic and endemic species marks them as highly important for conservation decisions.